Epidemiology of domestic violence among married women: a community based cross-sectional study - Vachhani, Pushti V.; Bhimani, Nishant R.; Purani, Shyamal K.; Kartha, Girija P. (International Journal Of Community Medicine And Public Health, 2017)
Background: Domestic violence is a global issue, reaching across national boundaries as well as socio-economic, cultural, racial and class distributions. Domestic violence is among the most underreported crimes worldwide for both men and women. Globally, the victims of domestic violence are overwhelmingly women, and women tend to experience more severe forms of violence. Methods: It was a Community based Cross-sectional study. The study was carried out in the rural and urban area of Surendranagar district. Total 600 married women of 15-49 years of age were selected randomly. The information gathered was based on self-administered questionnaire. Strict confidentiality was maintained. Results: Out of total 600 women, 38.5% were victims of domestic violence in one form or the other. Out of these 231 victims, 134 respondents were from rural area and 97 respondents were from urban area. The study results revealed that age at marriage, literacy status of women and their husband, their occupational status, type of family and socio-economic class has significant impact on prevalence of domestic violence. Conclusions: Domestic violence is more prevalent among uneducated, backward and economically disadvantaged women.